2012
DOI: 10.1182/blood-2012-01-402123
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G enhances lymphoma cell radioresistance by promoting cytidine deaminase-dependent DNA repair

Abstract: APOBEC3 proteins catalyze deamination of cytidines in single-stranded DNA (ssDNA), providing innate protection against retroviral replication by inducing deleterious dC > dU hypermutation of replication intermediates. APOBEC3G expression is induced in mitogen-activated lymphocytes; however, no physiologic role related to lymphoid cell proliferation has yet to be determined. Moreover, whether APOBEC3G cytidine deaminase activity transcends to processing cellular genomic DNA is unknown. Here we show that lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 47 publications
8
72
2
Order By: Relevance
“…To interpret the functional impact of the changes observed it is important to keep in mind that: IFIT1 and IFIT3 are both implicated to function against viral infections (19); OASL functions in antiviral response (20); AZU1 serves as an important mediator during the initiation of the immune response (30); and APOBEC3G promotes cytidine deaminase-dependent DNA repair to render radiation resistance in lymphoma (48). In addition, IFN-inducible IFITM proteins (IFITM1, 2 and 3) inhibit the replication of various viruses including HIV-1 (21).…”
Section: Discussionmentioning
confidence: 99%
“…To interpret the functional impact of the changes observed it is important to keep in mind that: IFIT1 and IFIT3 are both implicated to function against viral infections (19); OASL functions in antiviral response (20); AZU1 serves as an important mediator during the initiation of the immune response (30); and APOBEC3G promotes cytidine deaminase-dependent DNA repair to render radiation resistance in lymphoma (48). In addition, IFN-inducible IFITM proteins (IFITM1, 2 and 3) inhibit the replication of various viruses including HIV-1 (21).…”
Section: Discussionmentioning
confidence: 99%
“…The prevailing notion of A3G being maintained under strict control, limiting its localization to the cytoplasm, has been brought into question by several studies that demonstrated it can be partially localized to the nuclear compartment (Stopak et al 2003;Hill et al 2006;Depboylu et al 2007). It has also been shown that A3G can be recruited to doublestrand breaks in genomic DNA (Nowarski et al 2012) and that it may shuttle to the nucleus in response against LINE-1 retrotransposition (Kinomoto et al 2007). A3G expression in the germline and its small nuclear fraction, both fundamental conditions for inherited mutagenesis, provide a window of opportunity for the contribution of A3G to genome evolution.…”
Section: Enzyme-induced Genome Evolution By Apobec3gmentioning
confidence: 99%
“…Interestingly, recent work from Halemano and co-workers showed evidence that mouse APOBEC3 mutates immunoglobulin heavy chain variable genes (IgV) during retroviral infections, demonstrating thereby a previously unidentified function of APOBEC3 in generating virus-specific neutralizing antibodies and highlighting a new mechanism for antibody diversification in vivo [50]. In addition, APOBEC3 has also been attributed a role in double-strand break (DSB) DNA repair by non-homologous end joining (NHEJ) [51,52]. Expression of APOBEC3G in lymphoma cells associates with efficient DSB repair, whereas inhibition of APOBEC3G expression or deamination activity results in impaired joining of DSBs by NHEJ, implying a prosurvival role of APOBEC3 in lymphoma cells [51].…”
Section: Introductionmentioning
confidence: 99%